Relationship between musculoskeletal pain, sleep quality and migraine with level of physical activity in college students during the COVID-19 pandemic. Issue 10 (October 2022) - Pedrosa Luna Oliveira, Juliana; Zangirolami-Raimundo, Juliana; Evaristo de Andrade, Paulo; Louise Pereira Lima, Soraya; Cavalcante Lima, Amanda Regina; de Abreu, Luiz Carlos; Raimundo, Rodrigo Daminello
Abstract: Background: The COVID-19 pandemic has negative impacts on general health of the population, social isolation can contribute to the emergence of various dysfunctions. Objective: To investigate the association musculoskeletal pain, sleep quality and migraine with the level of physical activity during the COVID-19 pandemic in college students. Method: Data were collected through a sociodemographic questionnaire containing questions regarding sample characterization, the Nordic Musculoskeletal Questionnaire (NMQ), Pittsburgh Sleep Quality Index (PSQI), Migraine Disability Assessment (MIDAS) and the International Physical Activity Questionnaire (IPAQ). Results: In the correlation made between the data at the beginning of the pandemic, there was a direct relationship between PSQI and the number of days with pain (p < 0.001), the Initial MIDAS score (p < 0.001) and the initial pain intensity (p < 0.001). There was a direct relationship between PSQI scores and age (p = 0.044), MIDAS (p < 0.001) and pain intensity (p < 0.001). We identified a direct relationship between MIDAS and the number of days with pain (p < 0.001) and pain intensity (p < 0.001). Conclusion: Social isolation, during the COVID-19 pandemic, probably potentiated painful symptoms in various parts of the body, worsening sleep quality and migraine. In addition, there is a strong evidence that the decrease in physical activity during the pandemic is associated with sleep quality, with the number of days with musculoskeletal pain and migraine. Abstract : COVID-19; Musculoskeletal pain; Migraine; Sleep wake disorders; Exercise.